Elective neck dissection in primary parotid carcinomas: A systematic review and meta‐analysis. (26th December 2020) - Borsetto, Daniele; Iocca, Oreste; De Virgilio, Armando; Boscolo‐Rizzo, Paolo; Phillips, Veronica; Nicolai, Piero; Spriano, Giuseppe; Fussey, Jonathan; Di Maio, Pasquale
Abstract: Background: To estimate the rate of occult cervical lymph node metastases in cN0 patients affected by primary parotid carcinomas and to scrutinize the evidence on the indication and extent of elective neck dissection in these neoplasms. Methods: Medline, Embase, Web of Science, Cochrane Library and Scopus were searched until August 31, 2020, to identify studies reporting the use of elective neck dissection in the management of malignant parotid tumours. The PRISMA checklist was used. A single arm meta‐analysis was then made to determine the pooled rate of occult lymph node metastases. Risk of bias of the included studies was assessed through the ROBINS‐E tool. Results: The initial search returned 20 541 articles, of which twelve met the inclusion criteria and were included in the meta‐analysis. They comprised 1310 patients with parotid carcinoma, of whom 542 cN0 underwent elective neck dissection, which led to the diagnosis of lymph node metastasis (pN+/cN0) in 113 cases. Meta‐analysis of the results of elective neck dissection showed an overall rate of occult metastases of 0.22 (99% CI: 0.14‐0.30). Locally advanced or high‐grade tumours were the commonest indications for elective neck dissection in the included studies. The most dissected lymph node levels were I‐II‐III, and level II was the commonest site of occult nodal metastases. Conclusions: An occult metastasis rate of 0.22 (99% CI: 0.14‐0.30) represents a not negligible percentage value, which should encourage further research to outline the most appropriate elective neck management in cN0 patients with parotid carcinomas.